BISCUIT FORMULATION WITH SUBSTITUTION OF BROWN RICE FLOUR - Widodo, Slamet; Sirajuddin, Saifuddin (Institut Pariwisata dan Bisnis Internasional, 2019)
Focus of this study was formulation of biscuit with substitutionof brown rice flour which were widely accepted by the community. The objective of the study was to formulate biscuit subtitution by brown rice flour. The experiment was conducted in Maret-July 2017 in Family Welfare Education Laboratory. Data collected was quality of biscuit (color, flavor, texture, taste, and overall) and the preference. Data was analyzed by Mean and ANOVA. Result: 18g wheat flour, 6g cornstarch, 4g tapioca starch, 19g brown rice flour, 12g margarine, 29g eggs yolk, and 12g refined sugar. Nutrition contents the best biscuit was water 2,52g, ash 1,19g, fat 24,46g, protein 11,68g, carbohydrate 60,15g, and energy 507,46Kcal.